2002
DOI: 10.1001/jama.287.13.1706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Leptin on Arterial Thrombosis Following Vascular Injury in Mice

Abstract: Leptin contributes to arterial thrombosis following vascular injury in vivo and these prothrombotic effects appear to be mediated through the platelet leptin receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
3
10

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(158 citation statements)
references
References 16 publications
4
139
3
10
Order By: Relevance
“…Consistent with a direct role of leptin in thrombosis, experimental studies have shown that ob/ob mice that are defective in leptin secretion, show impaired thrombus formation in response to vascular injury that is subsequently restored by leptin administration. [16][17][18] However, in the present study, the lack of robust correlation between leptin and platelet-MPs, a reliable marker of platelet activation, did not substantiate the view that leptin directly modulates platelet activation, even though leptin binding to its platelet receptor promotes aggregation. [16][17][18] Leukocyte-derived MPs could be key factors in pathways activated by obesity-mediated inflammation.…”
Section: Obesity Associated Inflammation and Vascular Damagecontrasting
confidence: 61%
“…Consistent with a direct role of leptin in thrombosis, experimental studies have shown that ob/ob mice that are defective in leptin secretion, show impaired thrombus formation in response to vascular injury that is subsequently restored by leptin administration. [16][17][18] However, in the present study, the lack of robust correlation between leptin and platelet-MPs, a reliable marker of platelet activation, did not substantiate the view that leptin directly modulates platelet activation, even though leptin binding to its platelet receptor promotes aggregation. [16][17][18] Leukocyte-derived MPs could be key factors in pathways activated by obesity-mediated inflammation.…”
Section: Obesity Associated Inflammation and Vascular Damagecontrasting
confidence: 61%
“…7 Although leptin's major role seems to be in the regulation of body weight and energy metabolism, several evidences suggest that this hormone could be involved in other pathophysiological mechanisms, such as immune function, angiogenesis, bone formation and fertility, and the expression of leptin receptor has been demonstrated in a variety of tissues. [8][9][10][11][12][13] The long form of leptin receptor (ObRb) has been found on platelet membrane, 14 and it has been demonstrated that leptin-deficient ob/ob mice, 15,16 and wild-type mice treated with a leptin-neutralizing antibody, 17 develop unstable thrombi and an attenuated thrombotic response to arterial injury, and they exhibit a defective platelet aggregation. Leptin also promotes thrombosis in the mouse, and it potentiates the aggregation of murine platelets in vitro in a leptin receptor-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…10 Recent studies demonstrate that leptin is able to accelerate arterial thrombosis; thus, suggesting a mechanism for atherothrombotic disease in obesity. 11,12 The long form of leptin receptor (ObRb) has been found on the platelet membrane, and it has been suggested that leptin may promote the aggregation of human platelets through the activation of its receptor and postreceptor phosphorylation of STAT proteins. 13 The ability of leptin to enhance platelet aggregation has been recently confirmed in ob/ob mice 11 and healthy subjects.…”
Section: Introductionmentioning
confidence: 99%